Response of Some Blood Immune System Variables After Two Different Aerobic Efforts for Long Distance Runners: Response of Some Blood Immune System Variables - Gorgees, Shatha Hazim (Indonesian Journal of Sport Management, 2024)
Aim: Know the importance of differences in values of pre-tests of two aerobic exercises (Sharki and Bruce) on some blood immune system variables for long-distance runners. Know the importance of differences in values of post-tests of two aerobic exercises (Sharki and Bruce) on some blood immune system variables for long distances runners Researcher hypothesized: No morally significant differences are found in values of pre-post tests of two aerobic exercises ( Sharki and Bruce ) on some blood immune system variables for long distance runners . researcher used descriptive method due to its appropriateness. society was (10) advanced players of Nineveh governorate for medium and long distances the sample were (6) long distances players representing (60%) chosen randomly chosen . the following statistical means were used ( t-test for related samples, standard deviation , mathematical means , variance factor ) Researchers found: Two aerobic exercises made moral change in WBC , MON , GRA (Glubiolin) Two aerobic exercises didnt make moral change in LYM variables Mathematical means of aerobic exercise (Sharki ) was higher than that of (Bruce ) Recommended: Necessity of periodical check for athletes in specialized athletic centers to know health status of athletes in general and immune system in particular. Makea study to study same variables on female athlets. Make a comparative study between male and female athlets regarding same variables and same and exercises